DEVELOPMENT OF POP-UP BOOK LEARNING MEDIA TO IMPROVE CLASS VII STUDENTS' MASTERY OF MUFRODAT MTs UINSU MEDAN LABORATORY - Sinaga, Emi Salsabila; Zulheddi, Zulheddi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims, 1) to describe the development of Pop-Up Book learning media to improve students' mastery of mufrodat, 2) to find out whether the development of Pop-Up Book learning media is effective in improving students' mastery of mufrodat in terms of validity, practicality and effectiveness of the media. This research is Research and Development (RD) research. This research was conducted at MTs Laboratory UINSU Medan with research subjects namely 20 students in class VII. The data analysis techniques used in this research are validity testing, practicality testing and effectiveness testing of learning media. Based on data analysis on the validity of learning media, it was obtained based on the results of media expert and material expert validation assessments, the media expert's assessment was 100% in the